Survey Partisipasi (Kemitraan) Dunia Usaha (Korporasi) dalam Rangka Menunjang Pembiayaan Pembangunan Daerah Jawa Timur - Bambang Banu Siswoyo; Syihabudhin -; Agus Dharmawan (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The development of SMEs through a partnership has been a lot done but its effectiveness is widely questioned by various parties concerned. For that, the understanding and selection patterns of partnership is very important nuances dependence put forward (Siswoyo, 2006). Implementation of the concept of interdependence is to implement the cooperation. In conditioned environments, build cooperation is a suitable alternative to be applied for reasons of cohesiveness. In an environment that has been stable partnership model can improve performance because it is like a lubricant in the gear-gear actor partnerships. Basing this needs to be done to reveal the existence of corporate research partnerships with the UMK organizers, which include (1) field and type of company, (2) mechanisms for the implementation of business cooperation, (3) fields and patterns of cooperation, (4) capacity building activities, (5) capability, (6) strategy implementation, (7) Sustainability of cooperation, (8) the problems faced, and (9) needs and expectations of development cooperation. Description 9 (nine) this variable describes the participation of the business in development in East Java, implementation, problems, benefits to the goals and expectations in future development.Keywords: kemitraan korporasi-UMK, pembiayaan pembangunan